Indirect current controlled shunt active power filter for power quality improvement - Mahanty R. (My University, 2025)
The paper deals with an indirect current controlled shunt active power filter (APF) for improving power quality by reactive power compensation and harmonic filtering. The proposed APF is based on a voltage source inverter (VSI). The VSI is controlled by two loops, the voltage control loop and the current control loop. The voltage control loop regulates the DC link capacitor voltage and the current control loop uses hysteresis band control to shape the source current such that it is in-phase with and of the same shape as the input voltage. The major advantage of the proposed APF is that the reference current for power quality improvement is generated from the DC link capacitor voltage. The proposed scheme has been verified through simulation and experimental investigations. © 2014 Elsevier Ltd. All rights reserved.